Comparative análisis between synthetic and natural grass for soccer, in terms of economy, social and sport rentability, in the university enviroment - J.A. Párraga; A. Sánchez (Asociación Española de Ciencias del Deporte, 2010)
In this work, we analyse the characteristics of a synthetic surface, last generation surface for soccer's practice. Due to the new technological advances, it have been obtained a flooring that reproduces the game in a very similars conditions to the ones we have in a natural grass field. In this study we have considered techniques, economicals and socials aspects as a reference gauge at the moment of taking decisions to select the type of surface, making a valuation of the advantages and disadvantages that this flooring suppose depending on the management necessity we want to obtain. Also we analyse the characteristics of the elements that shape the surface : type of fibber, length, density, etc.., and also we make some suggestions for its maintenance, marking and watering. At last (at the conclusions) we propose synthetic grass of last generation (sand-rubber) as a very best alternative for the practice of soccer, with highs indexes of quality, that increase the economical and social rentability, due to the bigger number of uses, and that in many cases it offers a bigger technique quality because it's difficult to arrange of natural grass fields in good conditions. KEY WORDS: Synthetic grass, economical, social and sport rentability.